Penggunaan Media Tumbuhan Dalam Peningkatan Kreativitas Menggambar Anak Usia 5-6 Tahun Di PAUD KB Anak Negeri Praya Kabupaten Lombok Tengah - Huswatul Hasanah; Gunawan Gunawan; Made Suwasa Astawa; Muazar Habibi (Indonesian Journal of Elementary and Childhood Education, 2023)
The problem of children's lack of creativity in drawing can be helped by using plants found in the surrounding environment, such as turmeric, young teak leaves, komak leaves, hibiscus flowers, horsewhip leaves, and grape stem charcoal. This research aims to increase children's drawing creativity through the use of plant media in Praya State KB Children's PAUD. This study used qualitative research methods. The subjects in this research were 10 students aged 5-6 years in group B at PAUD KB Anak Negeri Praya. Data collection techniques use observation, interviews and documentation. There are 20 observation instruments with discriptors. The data analysis used in this research is data analysis which consists of data collection, data reduction, data presentation, and drawing conclusions. The average on the first day was 64.88% in the starting to develop (MB) category, while the overall average of the children's drawing activity data on the second day was 89.63% in the very well developing (BSB) category. From the overall average data results, children's drawing activities on the second day experienced an increase. It was concluded that the use of plant media was proven to be able to develop the drawing creativity of children aged 5-6 years in PAUD KB Anak Negeri Praya, Central Lombok Regency.